2016
DOI: 10.1002/job.2086
|View full text |Cite
|
Sign up to set email alerts
|

A rigorous test of a model of employees' resource recovery mechanisms during a weekend

Abstract: SummaryEmployees' recovery from the effects of occupational stress can be affected by their actions during time away from work. Conservation of resources theory argues that a key to an effective stress recovery process is the replenishment of resources during off-work time (a weekend in the present study). We test a model of the stress recovery process during a weekend whereby two recovery mechanisms (weekend activities and recovery experiences) improve two personal resources (self-regulatory capacity and stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
99
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(115 citation statements)
references
References 88 publications
9
99
1
Order By: Relevance
“…It is known that physical and social activities are usually conducive to recovery, but findings regarding most other types of leisure activities (e.g., passive activities, like watching TV) are inconsistent (e.g., Sonnentag 2001;Sonnentag et al 2017). Although recovery experiences are presumed to underlie off-job activities (Sonnentag and Fritz 2007), little is known about which activities are linked to which experiences (e.g., Ragsdale and Beehr 2016). It is probably possible to get the same experiences from different activities and that the same activities may generate different experiences in different individuals (e.g., someone may find reading relaxing, whereas for someone else, it may produce mastery experiences).…”
Section: Limitations and Ideas For Future Researchmentioning
confidence: 99%
“…It is known that physical and social activities are usually conducive to recovery, but findings regarding most other types of leisure activities (e.g., passive activities, like watching TV) are inconsistent (e.g., Sonnentag 2001;Sonnentag et al 2017). Although recovery experiences are presumed to underlie off-job activities (Sonnentag and Fritz 2007), little is known about which activities are linked to which experiences (e.g., Ragsdale and Beehr 2016). It is probably possible to get the same experiences from different activities and that the same activities may generate different experiences in different individuals (e.g., someone may find reading relaxing, whereas for someone else, it may produce mastery experiences).…”
Section: Limitations and Ideas For Future Researchmentioning
confidence: 99%
“…In particular, it was observed that psychological detachment, relaxation, recovery of resources, and psychological stability are not proportional to the quantity of weekend activities but vary according to individual characteristics and the degree of personally perceived recovery experiences [26]. In this respect, this study seeks to broaden the understanding in four areas [16][17][18].…”
Section: Introductionmentioning
confidence: 97%
“…As a means of coping with job stress, weekend activities and recovery experiences have been attracting public interest, which has fueled a surge of related research [14][15][16][17][18]. However, previous studies on job stress and psychological well-being have addressed the issue from an organizational perspective [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that NA is negatively related to personal accomplishment (a dimension of burnout), because people with higher NA tend to perceive situations as hindrances (Alarcon, Eschleman, & Bowling, ). Previous research has shown that low‐effort activities may be weakly related or unrelated to mastery (e.g., Ragsdale & Beehr, ), possibly because any potential for learning or experiencing challenge comes from more passive behaviours (e.g., watching a cooking show or trivia show). However, in line with the research noted above, we expect that this relationship will become negative for people with higher NA.…”
Section: Introductionmentioning
confidence: 99%